Pendidikan Entrepreneurship dalam Membentuk Kecerdasan Emosional Santri Pondok Pesantren Darul Ihsan Menganti Gresik - Muhammad Ilham; Abdul Halim; Barudin (Jurnal Pendidikan Agama Islam Miazhar, 2023)
Entrepreneurship education is an attitude and ability to create something new, or innovate old products or services into new products or services that are more useful and have high economic value. This study aims to describe and explore entrepreneurship education in the formation of students' emotional intelligence. The aims of this study are 1) to describe the concept of entrepreneurship education at Darul Ihsan Menganti Islamic Boarding School in Gresik. 2) To describe the implementation of entrepreneurship education at Ponpes Darul Ihsan Menganti Gresik. 3) To describe the impact of entrepreneurship education on the formation of emotional intelligence of students at Ponpes Darul Ihsan Menganti Gresik. To achieve these objectives, researchers used qualitative research methods. Data collection techniques used in the form of observation and interviews. Interview subjects in this study consisted of caregivers of Islamic boarding schools, coordinators of implementing entrepreneurship education, and several students. While the subject of observation are several male students and female students. The results of this study are: First, all entrepreneurial activities carried out by students are the concept of Berkhidmah or the dedication of students to the kyai. Where the concept of khidmah, for the field of entrepreneurship at this time is called Entrepreneurship education. Second, the implementation of entrepreneurship education activities at Darul Ihsan Menganti Islamic Boarding School in Gresik is divided into several fields of activity carried out by students, namely cooperatives, culinary, Anugerah Water refill depots, Laundry Services and also in the transportation sector of Anugerah Abadi Trans. Third, this entrepreneurship education also has an impact on the students' self-development process, namely training them to be mentally strong, confident, not giving up easily, being patient, being able to maintain relationships with their partners, and of course being able to control their emotions.